A Novel Loop-Mediated Isothermal Amplification Assay for Serogroup Identification of Neisseria meningitidis in Cerebrospinal Fluid - Lee, DoKyung; Kim, Eun Jin; Kilgore, Paul E.; Takahashi, Hideyuki; Ohnishi, Makoto; Tomono, Jun; Miyamoto, Shigehiko; Omagari, Daisuke; Kim, Dong Wook; Seki, Mitsuko (Frontiers in Microbiology, 2016)
We have developed a novel Neisseria meningitidis serogroup-specific loop-mediated isothermal amplification (LAMP) assay for six of the most common meningococcal serogroups (A, B, C, W, X, and Y). The assay was evaluated using a set of 31 meningococcal LAMP assay positive cerebrospinal fluid (CSF) specimens from 1574 children with suspected meningitis identified in prospective surveillance between 1998 and 2002 in Vietnam, China, and Korea. Primer specificity was validated using 15 N. meningitidis strains (including serogroups A, B, C, E, W, X, Y, and Z) and 19 non-N. meningitidis species. The N. meningitidis serogroup LAMP detected down to ten copies and 100 colony-forming units per reaction. Twenty-nine CSF had N. meningitidis serogroup identified by LAMP compared with two CSF in which N. meningitidis serogroup was identified by culture & multi-locus sequence typing. This is the first report of a serogroup-specific identification assay for N. meningitidis using the LAMP method. Our results suggest that this assay will be a rapid, sensitive and uniquely serogroup-specific assay with potential for application in clinical laboratories and public health surveillance systems.